Efficacy of rubber band ligation in third degree hemorrhoid - Shrestha, Samir; Shah, S; Shrestha, J; Shah, JN (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Introduction: Rubber band ligation (RBL) is an effective treatment in symptomatic 1st and 2nd degree hemorrhoids. The aim of this study was to assess the outcome, effectiveness and complications RBL as out patient procedure for symptomatic 3rd degree hemorrhoids.Method: Seventy one patients with symptomatic third degree hemorrhoids underwent rubber band ligation in the department of surgery at National Academy of Medical Sciences, Patan hospital and Shree Birendra Army hospital. Nine defaulters were excluded from the study and data on 62 patients were analysed. Outcome measures were symptomatic cure i.e. stoppage of bleeding and reduced mucosal prolapse. Complications were categorized as immediate (within 1 hour), early (within one week) and late (within 6 weeks).Result: There was symptomatic improvement (stoppage of bleeding and reduced mucosal prolapse) in 47 (75.8%)  patients. Four patients required repeat banding. In 15 (24.2%) patients hemorrhoidectomy was performed due to failure of RBL. Pain and bleeding was common immediate and intermediate complication respectively.Conclusion: Rubber band ligation is an effective, outdoor procedure for symptomatic 3rd degree hemorrhoids with acceptable morbidity.